Comparison of the Effects of Propofol Anaesthesia and Desflurane Anaesthesia on Neutrophil/Lymphocyte Ratios After Coronary Artery Bypass Surgery (Annals of Medical Research, 2021)
None
Keywords: Coronary Artery Surgery; Propofol And Desflurane Anesthesia; Neutrophil/Lymphocyte Ratio.